CONSTRUCTION OF GRAPH ANALYTICAL MODEL OF OPTICAL EYE SYSTEMS IN MATLAB-3DS ENVIRONMENT MAX - Troyanov , P. P.; Zamkovy, D. V.; Troyanov , D. P. (Problems of Informatization and Management, 2021)
Based on the schematic image of the eye proposed by Gulstrand and the accommodation artificial lens, a graph-analytical model is created, which is a 6-element three-dimensional image. Matlab-3ds max medium was used to build such a model. It can be used to conduct a hypothetical experiment to study the process of accommodation of the optical system of the eye.